The incidence and patterns of hardware failure after separation surgery in patients with spinal metastatic tumors - Amankulor, Nduka M.; Xu, Ran; Iorgulescu, J. Bryan; Chapman, Talia; Reiner, Anne S.; Riedel, Elyn; Lis, Eric; Yamada, Yoshiya; Bilsky, Mark; Laufer, Ilya (The spine journal, 2014)
Background context - Spine metastases occur frequently in patients with cancer. A variety of surgical approaches, including anterior transcavitary, lateral extracavitary, posterolateral, and/or combined techniques are used for spinal cord decompression and restoration of spinal stability. The incidence of symptomatic hardware failure is unknown for the majority of these approaches. - Purpose - The purpose of this study was to determine the incidence of symptomatic hardware failure and the associated risk factors in patients with metastatic epidural spinal cord compression (MESCC). - Study design/setting - This was a retrospective study. - Patient sample - The current series analyzes a cohort of 318 patients who underwent separation surgery, which involves single-stage posterolateral decompression and posterior segmental instrumentation for MESCC. - Outcome measures - The event of interest was hardware failure; the competing event was death resulting from any cause. All patients were monitored for survival analysis. A competing risk analysis was conducted to examine univariately a number of potential risk factors associated with hardware failure, including junctional level, gender, construct length, and the presence or absence of prior chest wall resection. - Methods - A retrospective analysis and chart review were performed for 318 consecutive patients who underwent posterolateral decompression and posterior screw-rod fixation without supplemental anterior fixation from March 2004 to June 2011 at our institution. The median follow-up time for survivors without hardware failure was 399 days (range, 9-2,828), with a mean operative time of 3 hours. A total of 78% of patients died during the 7-year study period. - Results - Of the 318 patients, nine (2.8%) exhibited signs and symptoms of hardware failure and required revision of the instrumentation. Patients with chest wall resection and those with initial construct length greater than six contiguous spinal levels exhibited a statistically significantly higher risk of symptomatic hardware failure than their counterparts. We observed a trend toward an increased risk of failure in women compared with men (p=.09). - Conclusions - The incidence of hardware failure is low in patients with MESCC who undergo posterolateral decompression and posterior screw-rod instrumentation. Moreover, the short operative time and low morbidity profile associated with this approach make it a reliable and acceptable method for the surgical treatment of MESCC. Patients with constructs spanning six or more levels or those with prior chest wall resection are at higher risk for instrumentation failure.